Existence of Witness and Victim Protection Agencies in the Perspective of Justice for Victims Domestic Violence - Oktir Nebi; Sukamto Sutoto; Hafrida; Elly Sudarti (International Journal of Integrative Sciences, 2024)
The objective of this research is to examine the functioning of institutions responsible for safeguarding witnesses and victims in ensuring justice, advantages, and legal assurance for individuals affected by domestic violence. The chosen research method is Normative Juridical, also known as Normative research. Despite the Witness and Victim Protection Agency fulfilling its responsibilities to protect victims of domestic violence, it is not the primary choice for those seeking protection. To address this, there is a need to extend the reach of the Witness and Victim Protection Agency beyond the National Capital to include representatives in all Provincial Capitals across Indonesia. Additionally, empowering these representatives to make decisions on protection requests from domestic violence victims is crucial. Furthermore, there is a necessity to formalize the institutional relationships between the Witness and Victim Protection Agency and other relevant organizations. This would enhance protection services tailored to the specific requirements of domestic violence victims. This could involve establishing institutional connections to improve the overall effectiveness of victim protection efforts